Strategic Evolution Of Digital Transformation And Information Technology Governance: A Systematic Literature Review - Zulistia Salsabila; Hamdani (SHM Publisher, 2026)
Digital transformation and information technology (IT) strategy have become critical pillars of contemporary organizational management. This article presents a systematic literature review of 80 articles published between 2020 and 2025 in reputable international journals indexed in Scopus and/or Web of Science. The review examines digital transformation and IT strategy within business and organizational management using the PRISMA protocol and a structured thematic synthesis approach. The analysis covers digital transformation strategy, IT governance and strategic alignment, cloud computing and IT infrastructure, big data analytics and business intelligence, artificial intelligence, digital leadership and change management, cybersecurity, e-business and digital innovation, and enterprise resource planning and system integration. A systematic coding process was used to extract and synthesize bibliographic information, research methods, organizational contexts, key constructs, and major findings. The review shows that digital transformation is a multidimensional process of organizational change that extends beyond technology adoption and depends on the interaction of strategy, leadership, culture, governance, and the broader business ecosystem. It also highlights research gaps concerning developing-country contexts, integration across research themes, and sustainability. These findings provide an integrated overview of the field and inform a future research agenda for scholars and practitioners.